Pelatihan Pemasaran Produk Umkm Melalui Platform Digital Sebagai Upaya Meningkatkan Kesejahteraan Masyarakat Desa Madiredo Kecamatan Pujon - Abd. Mu'id Aris Shofa; Mifdal Zusron Alfaqi; Alfian Fawaidil Wafa; Zulfikar Waliyuddin Fattah (Perkumpulan Dosen Program Hibah Indonesia (PDPHI), 2024)
Madiredo Village is one of the villages in Pujon District, Malang Regency, East Java. Madiredo Village has a lot of potential natural products that support sales in the MSME sector. However, in its implementation there are obstacles faced by MSMEs in Madiredo Village, namely the marketing process of the products produced. Therefore, training is needed to improve the quality of sales on digital platforms. The method used is the FGD and Workshop method. The activity participants consisted of teenagers who were members of the Madiredo Village Youth Organization. The results of this activity are better E-commerce management than before, an attractive and more updated product packaging display, and a more trendy and complete online shop appearance